STUDY OF GILL, KIDNEY, AND LIVER STRUCTURE OF Pangasius hypophthalmus IN THE TANJUNG KUDU LAKE AND SAIL RIVERS, RIAU PROVINCE - Irene, Christin; Eddiwan, Eddiwan; Windarti, Windarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Environmental condition and water quality in general may affects the health status of fish and it represents in the structure of fish organs such as the gill, kidney, and liver. To understand the structure of the gill, kidney, and liver of Pangasius hypophthalmus that live in the Tanjung Kudu Lake (good water quality) and in the Sail River that has been polluted, a study has been conducted from November to December 2020. Twelve fishes (6 fishes/river) were analyzed. The tissue was formalin-fixed and processed through alcohol series, paraffin-embedded, 5m sliced and Hematoxylin-Eosin stained. The histological samples were then studied using a binocular microscope Olympus CX 21. The abnormality level of the tissue was categorized using the Histopathological Alteration Indeks (HAI). Results showed that the fish tissues from both study sites indicate light abnormality signs such as hyperplasia, hypertrophy, and lifted epithelia. The HAI was 2 for fish from the Tanjung Kudu Lake and 3 for the fish from the Sail River. This index indicates that the abnormality may be cured as the water quality improved.